PENGARUH MODEL PROBLEM BASED LEARNING (PBL) BERPENDEKTAN KEARIFAN LOKAL TERHADAP KETERAMPILAN BERPIKIR KRITIS PESERTA DIDIK FASE E - Novel Wahyu Danissih, Putri; Ardi; Fadilah, Muhyiatul; Olvia Rahmi, Fitri (Universitas Cokroaminoto Palopo, 2024)
The purpose of this study was to determine the effect of the PBL model with a local wisdom approach on students' critical thinking skills. Local wisdom-based learning is also one of the efforts that teachers can make to introduce learning with a contextual approach that is full of real experiences while helping to maintain the noble values ​​of local wisdom in their area, which are very much needed by students. This study uses an experimental method with a randomized control-group pretest posttest design that compares the results of the Pretest and Posttest. From the research results, it can be seen that the hypothesis test shows a sig. (2-tailed) value <0.05, which is at 0.00. This proves that there is an increase in students' critical thinking skills after implementing problem-based learning (PBL) with a local wisdom approach. So from these results it can be shown that H1 is accepted, namely that the problem-based learning model with a local wisdom approach has a positive effect on students' critical thinking skills.